Comparison of hematological and biochemical parameters in COVID-19 pneumonia patients before and after convalescent plasma (CP) treatment: COVID-19 pneumonia and convalescent plasma treatment - Polat, Esra; Ürkmez, Fatma Yekta (Journal of Surgery and Medicine, 2022)
Background/Aim: Convalescent plasma (CP) therapy, which includes processing and administering antibody-rich plasma from recovered patients to sick patients, is used for passive immunity in COVID-19 pneumonia patients in addition to antivirals and antibiotics. This study aimed to assess whether CP treatment significantly affects hyperviscosity and COVID-19 prognosis-related blood parameters. Methods: This study was a single-center retrospective cohort study. Ninety-seven patients with COVID-19 polymerase chain reaction (PCR)-positive results and pneumonia observed on thoracic computed tomography (CT) were included. Patients’ ferritin, d-dimer, C-reactive protein (CRP), and complete blood count levels before and after CP administration were compared. Results: Ferritin, d-dimer, white blood cell (WBC), neutrophil, and plateletcrit (PCT) levels and the platelet distribution width (PDW) were significantly higher and there was a significant decrease in the CRP level after CP treatment compared to before CP (P < 0.05). Ferritin, d-dimer, and CRP values measured after CP were higher in deceased patients than in survivors (P = 0.001, P = 0.007, and P < 0.001, respectively) Conclusion: Ferritin, d-dimer, WBC, and neutrophil levels, which we expected to decrease on the basis of the COVID-19 prognosis, unfortunately increased, and only CRP levels decreased. However, we found that these increases were more pronounced in patients who died. Considering these prognostic factors, the findings of our study suggest that CP treatment has no effect on the COVID-19 disease course and may lead to a worse prognosis.